More than a match? Assessing the HRM challenge of engaging employers to support retention and progression. (21st November 2017) - Sissons, Paul; Green, Anne E.
Abstract : This article considers employer engagement within a changing landscape of active labour market policy (ALMP). Employer engagement in ALMP has focused on supporting job entry for disadvantaged groups, through working with employers to attain changes on the demand side or using dialogue with employers to implement changes on the supply side. Employer engagement in this model is orientated to a point in time: the job match. However, ALMP policy in the UK is beginning to give greater emphasis to the sustainability of job entries and progression opportunities. This potentially creates a quite different set of expectations around employer engagement and asks more of employers. Yet securing strong engagement from employers in ALMP has tended to be difficult. This article examines the challenges that such a change in focus will have for existing models of employer engagement and on associated implications for HRM theory, policy and practices.